The post-truth discourse and the politics of memory in the contemporary media spaces - Кирило Мєлєкєсцев (Cхід)
This article concerns the emergence, definition, and characteristic of the phenomenon of “post-truth” and how its characteristics are used in connection with historical narratives by various political forces for their own goals. The article’s goal is to identify how historical narratives are used by the spreaders of post-truth for various results in domestic and foreign policy, or, in the case of the post-truth spreader being a contesting politician vying for power, for electoral support. The research utilizes historical-narrative and historical-comparative methods, alongside methods of discourse and content analysis. After reviewing the literature, it is observed that from the point of view of historical politics, the methods of spreading the post-truth pose a tempting prospect of ensuring the ideological unity of the nation (or a part of it). The creation of an ideological and informational climate in which history consisted only of the heroism of "Us" and the various affronts and capture of “our old territories” by "the Other" contributes to internal stability. However, such historical politics, while useful in an “information bubble” in domestic policy, can be easily exposed and deconstructed by the neighboring powers decried as “the Other”, blamed for various historical grievances (in the case of a reigning regime using post-truth historical narratives), or by political rivals debunking false claims (in the case of a contesting political force using such narratives in a democracy). The post-truth relies on charisma and cognitive bias, rather than specific historical knowledge, and can be used to strengthen existing political support, more so than converting others. Post-truth accelerates the involvement of media consumers and the growth of their confidence in the correctness of the ideology. However, regardless of its utilitarian positives for political forces, a choice in favor of post-truth is a voluntary choice in favor of misinformation, anti-intellectualism and deception.